2020
DOI: 10.1177/0886260519898433
|View full text |Cite
|
Sign up to set email alerts
|

Gay, Bisexual, and Queer Men’s Attitudes and Understandings of Intimate Partner Violence and Sexual Assault

Abstract: Gay, bisexual, and queer (GBQ) men experience significant rates of intimate partner violence (IPV) and sexual assault (SA); however, there is limited research into their attitudes and understandings of IPV and SA. This article presents the findings of a 2018 survey of 895 GBQ men currently residing in Australia, focused on their views and experiences of healthy and unhealthy relationships. The survey included quantitative and open-ended qualitative questions. The findings presented in this article are primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…There has been growing scholarly interest in the topics of unwanted sex and sexual violence among gay, bisexual, queer, and other men who have sex with men (GBM) (Felix et al, 2021;De La Ossa, 2016;McKie et al, 2020;Salter et al, 2020;Sternin et al, 2021). Approximately 30%-47% of GBM report experiencing a sexual assault over their lifetime (Black et al, 2011;Chen et al, 2020;Rothman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There has been growing scholarly interest in the topics of unwanted sex and sexual violence among gay, bisexual, queer, and other men who have sex with men (GBM) (Felix et al, 2021;De La Ossa, 2016;McKie et al, 2020;Salter et al, 2020;Sternin et al, 2021). Approximately 30%-47% of GBM report experiencing a sexual assault over their lifetime (Black et al, 2011;Chen et al, 2020;Rothman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…power analyses (α = .05, 1 − B = .80), with small effect sizes (V = .114−.156). However, our sample size reflects prior research with SGM participants who reported situations where they could intervene (Salter et al, 2021).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Gender norms stem from gender stereotypes, such as the characterization of men as strong and tough, and women as emotional and domestic (Davies, 2002; Sorenson & Thomas, 2009). Personal acceptance or perceived acceptance of gender norms can negatively influence bystander behavior, as the bystander may not view the victim as needing or deserving help (Brown & Messman-Moore, 2010; Salter et al, 2021). For example, bystanders are generally more likely to intervene for victims who are stereotyped as being more feminine or “weaker” and needing more help (Sorenson & Thomas, 2009).…”
Section: Bystander Characteristics and Beliefsmentioning
confidence: 99%
“…Extensive research has been conducted on gender differences in bystander behavior, and women are generally more likely to intervene as bystanders and show more concern for the victim than do men (Bennett et al, 2017; Seelau et al, 2003). Gender differences in bystander behavior may be linked to increased recognition or efficacy of warning signs, increased empathy for the victim, and/or lack of endorsement of traditional gender norms and rape myths (Davies, 2002; National Coalition of Anti-Violence Programs, 2016; Salter et al, 2021). These potential explanations of gender differences in bystander behavior may also apply to other individuals from sexual and gender minority groups (Hoxmeier et al, 2022).…”
Section: Bystander Characteristics and Beliefsmentioning
confidence: 99%